Efisiensi Kerajinan Mebel di Pulau Giliraja Dalam Mengembangkan Kreativitas Bagi Masyarakat di Desa Banmaling Kecamatan Giligenting - Nurul Afifah (Jurnal Al-Tatwir, 2023)
The furniture industry in Indonesia is highly competitive, with many local and international companies operating within it. This intense competition is caused by several factors such as a large number of players in the market, similar products, and constantly changing consumer demand. To compete in this competitive market, furniture businesses must be able to develop effective marketing strategies. Overall, the furniture industry in Banmaling experienced a decline from 2019 to 2022. Therefore, a measurement of business efficiency was carried out to identify the factors causing the decline in business performance. This is aimed at determining policies and steps to improve business performance. The aim of this research is to explore the community development through furniture craft in Banmaling Village, Giligenting District. This research employs a qualitative research method with data collection techniques such as interviews, observations, and document analysis. This paper presents the results of an analysis of the technical efficiency level of furniture businesses in Banmaling in 2022. From the research and discussion, it can be concluded that 38.70% of furniture businesses in Banmaling have been efficient, while 61.3% have not been efficient with an average technical efficiency value of 68.69. Therefore, mentoring from the government, universities, and other relevant institutions is needed to improve furniture businesses in Serenan by providing additional capital and training in production management, human resources, finance, marketing, and other areas. This is expected to improve its technical efficiency level.